2022
DOI: 10.1093/humrep/deac036
|View full text |Cite
|
Sign up to set email alerts
|

The ABC of reproductive intentions: a mixed-methods study exploring the spectrum of attitudes towards family building

Abstract: STUDY QUESTION What are the intentions of men and women of reproductive age in the UK regarding reproduction and family building? SUMMARY ANSWER We identified six main categories of people; Avoiders, Betweeners, Completers, Desirers, Expectants and Flexers, for whom reproduction education strategies should be tailored differently to suit intentions. WHAT IS KNOWN ALREADY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Getting the message right also means that custom-made and personalized approaches are needed as people have different desires regarding family building which can change through the life course. Grace et al (2022) recently drew up a typology to distinguish between different categories of people according to their reproductive intention, thus identifying what they labelled as Avoiders, Betweeners, Completers, Desirers, Expectants, and Flexers. People in these different categories have different reproductive health information needs.…”
Section: Tailoring Messagesmentioning
confidence: 99%
“…Getting the message right also means that custom-made and personalized approaches are needed as people have different desires regarding family building which can change through the life course. Grace et al (2022) recently drew up a typology to distinguish between different categories of people according to their reproductive intention, thus identifying what they labelled as Avoiders, Betweeners, Completers, Desirers, Expectants, and Flexers. People in these different categories have different reproductive health information needs.…”
Section: Tailoring Messagesmentioning
confidence: 99%
“…This suggests language and educational messages about the relevance and importance of preconception health need to be inclusive of the multiple phases that people move through during their reproductive years in relation to their goal to become, or not become, a parent. [30][31][32] Information on all aspects of preconception health should be communicated through research study participant materials and public health messages, to ensure it resonates with people of reproductive age. Public contributors in our consultation concluded that general messages and recruitment text that are relevant to 'everyone' of reproductive age would be important to raise widespread awareness and normalise the concept of preparing for pregnancy and parenthood in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents cited occupational settings as a good environment for providing support and education. For example, young professionals who are yet to start a family, would be the ideal target audience for information on family building within the workplace [39] as the acceptance of, previously perceived as taboo topics continues to increase as people's reproductive health needs evolve over time [40]. For example, in recent times, previously taboo topics like mental health issues and mindfulness are being widely discussed in the professional environment [41,42].…”
Section: Discussionmentioning
confidence: 99%